Diseño de un modelo administrativo de mejoramiento de la calidad en el servicio posventa prestado por la empresa ORVISA S.A – sucursal Tarapoto, para el trimestre 2015 - Guevara Mas, Lenin (2015)
The aim of this study is to design an Administrative Model Quality Improvement in the after sales service provided by the company Orvisa SA - Sucursal Tarapoto, for the first quarter 2015, in which the needs and expectations of customers are identified and the processes they agree directly on the satisfaction of these, this in order to ensure the process of handling complaints and customer complaints. Branch Tarapoto - non-experimental design transversal character, for which it was conducted a study using the inductive method, based on experimental sample and the portfolio of the company Top100 Orvisa SA was used. According to the experimental procedure adopted for this study, data obtained from research tool express strengths and weaknesses in the offered sales service, factors that are reflected in direct dissatisfaction of the end customer and loyalty, also, the lack of tools to make good decisions when you receive a complaint or grievance. the main factors that generate dissatisfaction on the user, as the delay in resolving the complaint and claim the client, this excessive constraint is added to provide accurate and adequate information detailing procedures to be performed for decision-making and time were determined I offered product delivery service.